An assessment instrument of mind map product to assess students' creative thinking skill - Regina Ratih Fardhila; Edi Istiyono (REID (Research and Evaluation in Education), 2019)
Education is now more demanding for students to think more at a higher and more complex level. Mind map also builds creativity because it is more flexible in expressing ideas. The result of need assessment was the teachers cannot put on equation about creative thinking in test because the input of heterogeneous students, but they carried out project and practicum assessments, which required relatively much time, place and equipment. Therefore, the researchers develop instruments for assessing students' creative thinking skills at the high-school level trough mind map on valid and reliable biology subjects so that teachers can use them as a more efficient assessment tool. This research employed research and development (RD) method; adapting ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model. Content validity was achieved using the Lawshe method; CVR formula, while the construct validity was achieved through exploratory factor analysis with the SPSS program and then confirm with confirmatory factor analysis using Lisrel program. It is found out that the construct validity was proven by the significant value of MSA and Loading Factor value. Suitability of the construct model with the data was indicate with p-value= 0.68 (≥0.05); Root Mean Square Error Approximation = 0.00 (≤0.08); and Goodness of Fit Index= 0.94 (0.90). The reliability of the instrument is 0.774, which means reliable. The assessment instrument of mind map product to assess creative thinking skill of students at the high school level in biology subjects has ten fit items in four factors; Flexibility, Elaboration, Originality, and Fluency.